The Clinical Uses of Electrocochleography - Gibson, William P. (Frontiers in Neuroscience, 2017)
The clinical uses of electrocochleography are reviewed with some technical notes on the apparatus needed to get clear recordings under different conditions. Electrocochleography can be used to estimate auditory thresholds in difficult to test children and a golf club electrode is described. The same electrode can be used to obtain electrical auditory brainstem responses (EABR). Diagnostic testing in the clinic can be performed with a transtympanic needle electrode, and a suitable disposable monopolar electrode is described. The use of tone bursts rather than click stimuli gives a better means of diagnosis of the presence of endolymphatic hydrops. Electrocochleography can be used to monitor the cochlear function during surgery and a long coaxial cable, which can be sterilized, is needed to avoid electrical artifacts. Recently electrocochleography has been used to monitor cochlear implant insertion and to record residual hearing using an electrode on the cochlear implant array as the non-inverting (active) electrode.